ChemInform Abstract: Investigation of Magnetic Properties and Electronic Structure of Layered‐Structure Borides AlT2B2 (T: Fe, Mn, Cr) and AlFe2‐xMnxB2. Issue 18 (May 2015) - Chai, Ping; Stoian, Sebastian A.; Tan, Xiaoyan; Dube, Paul A.; Shatruk, Michael
Abstract The title compounds are characterized by powder XRD, magnetic measurements, Moessbauer spectroscopy, and DFT band structure calculations.